TP53 Germline Variations Influence the Predisposition and Prognosis of B-Cell Acute Lymphoblastic Leukemia in Children - Qian, Maoxiang; Cao, Xueyuan; Devidas, Meenakshi; Yang, Wenjian; Cheng, Cheng; Dai, Yunfeng; Carroll, Andrew; Heerema, Nyla A; Zhang, Hui; Moriyama, Takaya; Gastier-Foster, Julie M; Xu, Heng; et al. (Journal of clinical oncology, 2018)
Purpose Germline TP53 variation is the genetic basis of Li-Fraumeni syndrome, a highly penetrant cancer predisposition condition. Recent reports of germline TP53 variants in childhood hypodiploid acute lymphoblastic leukemia (ALL) suggest that this type of leukemia is another manifestation of Li-Fraumeni syndrome; however, the pattern, prevalence, and clinical relevance of TP53 variants in childhood ALL remain unknown. Patients and Methods Targeted sequencing of TP53 coding regions was performed in 3,801 children from the Children's Oncology Group frontline ALL clinical trials, AALL0232 and P9900. TP53 variant pathogenicity was evaluated according to experimentally determined transcriptional activity, in silico prediction of damaging effects, and prevalence in non-ALL control populations. TP53 variants were analyzed for their association with ALL presenting features and treatment outcomes. Results We identified 49 unique nonsilent rare TP53 coding variants in 77 (2.0%) of 3,801 patients sequenced, of which 22 variants were classified as pathogenic. TP53 pathogenic variants were significantly over-represented in ALL compared with non-ALL controls (odds ratio, 5.2; P < .001). Children with TP53 pathogenic variants were significantly older at ALL diagnosis (median age, 15.5 years v 7.3 years; P < .001) and were more likely to have hypodiploid ALL (65.4% v 1.2%; P < .001). Carrying germline TP53 pathogenic variants was associated with inferior event-free survival and overall survival (hazard ratio, 4.2 and 3.9; P < .001 and .001, respectively). In particular, children with TP53 pathogenic variants were at a dramatically higher risk of second cancers than those without pathogenic variants, with 5-year cumulative incidence of 25.1% and 0.7% ( P < .001), respectively. Conclusion Loss-of-function germline TP53 variants predispose children to ALL and to adverse treatment outcomes with ALL therapy, particularly the risk of second malignant neoplasms.